2021
DOI: 10.1097/njh.0000000000000722
|View full text |Cite
|
Sign up to set email alerts
|

Pride and Uncertainty

Abstract: There is limited knowledge about the psychosocial stress among the nursing staff working on the COVID-19 wards. This article reports on the experiences of frontline health care workers as it was described to supervisors counseling the nursing staff engaged in the response to the outbreak of COVID-19. Frontline health care workers, nurses, and nurses' aides experienced major work changes. Some were transferred to the newly formed COVID-19 wards in a large Danish hospital, were given new tasks, and had to collab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
2
5
1
2
Order By: Relevance
“…The choice to reject the vaccine was based on both their understanding of the human body and the immune system due to the training they had received as healthcare professionals and their personal knowledge of their own health status. The choice also demonstrated a shift in the level of fear of the disease and was different from a previous study from Denmark, in which the nursing staff at a COVID-19 ward during the first wave in early 2020 had greater uncertainty and fear of the disease [27]. It was unclear if this shift occurred because the participants in our study did not directly care for patients with COVID-19, the fluctuation in the number of people infected with COVID-19 or the increased knowledge of the disease that resulted in more confidence.…”
Section: Discussioncontrasting
confidence: 85%
“…The choice to reject the vaccine was based on both their understanding of the human body and the immune system due to the training they had received as healthcare professionals and their personal knowledge of their own health status. The choice also demonstrated a shift in the level of fear of the disease and was different from a previous study from Denmark, in which the nursing staff at a COVID-19 ward during the first wave in early 2020 had greater uncertainty and fear of the disease [27]. It was unclear if this shift occurred because the participants in our study did not directly care for patients with COVID-19, the fluctuation in the number of people infected with COVID-19 or the increased knowledge of the disease that resulted in more confidence.…”
Section: Discussioncontrasting
confidence: 85%
“…Their participants described psychological growth, increased professional identity and pride, with simultaneous positive and negative emotions (Sun et al, 2020 ). In another study, healthcare workers in Denmark described increased pride and wanting to be part of something bigger that created a balance with the COVID-related distress they were experiencing (Marsaa et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative studies from around the world reported on healthcare workers experiences during the COVID-19 pandemic, and documented their struggles and triumphs (Al-Ghunaim et al, 2021 ; Hoernke et al, 2021 ; Marsaa et al, 2021 ; Parsons Leigh et al, 2021 ; Q. Liu et al, 2020 ; Y. E. Liu et al, 2020 ; Yau et al, 2021 ). A systematic review of 28 qualitative studies examining the psychosocial impact of the pandemic on nurses revealed 3 main theses (Xu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Expanding an out-patient clinic with such an accompanying function, it will require organizational changes [ 20 , 47 ], and that it can create uncertainty in the nurse group when they are given new professional responsibility, this can in the worst case lead to stress and burn out [ 40 , 48 ]. However, we also know that through organization in palliative care, such as supervision and interdisciplinary collaboration, burn-out can be reduced [ 44 ].…”
Section: Discussionmentioning
confidence: 99%